An Analysis of Traditional Grammar, Immediate Constituent Analysis, and X-Bar Syntax Theory - Yanuarius Yanu Dharmawan (Bandar Lampung University (UBL), 2014)
Daily usage of a language leads people to understand more about how the language is produced. The different understanding of a language leads to a different interpretation of the people who use it or even listen to it. Analyzing a human language is very important to minimize the miscalculation of the aspects inside the language. Letters which form a word and words or phrases which form a sentence are the parts that need to be examined. The analysis of those parts can be done in many ways. This paper presents three of many ways to analyze a sentence. They are traditional grammar, Immediate Constituent (IC) analysis, and X-bar theory. How the analysis works in understanding a sentence will be accompanied by a few examples that make them clearer. The paper will find out the weaknesses and the strengths of those analyzed through the explanations and examples.